CT Compared with Arthroscopy in Quantifying Glenoid Bone Loss - Griffith, James F; Yung, Patrick S. H; Antonio, Gregory E; Tsang, Polly H; Ahuja, Anil T; Chan, Kai Ming (American journal of roentgenology (1976), 2007)
This study investigated the accuracy of CT in determining the presence and severity of glenoid bone loss in patients with unilateral anterior shoulder dislocation. Fifty patients (45 males, five females; mean age, 28.7 years; age range, 14-56 years) with anterior shoulder dislocation underwent shoulder CT examination before arthroscopy (mean time interval between CT and arthroscopy, 28.5 days; range, 9-73 days). Thirteen (26%) of the 50 patients had a single dislocation, whereas the remaining 37 patients (74%) had recurrent dislocation (mean, 8.2 dislocations; range, 2-50 dislocations). Glenoid bone loss was evident in 41 (82%) of the 50 patients at arthroscopy. Compared with arthroscopy, CT had a sensitivity in detecting glenoid bone loss of 92.7%; specificity, 77.8%; positive predictive value, 95.0%; and negative predictive value, 70.0%. Three false-negative CT assessments had 5%, 10%, and 10% glenoid bone loss, respectively, at arthroscopy. Two false-positive CT assessments had 8.7% and 5.7% glenoid bone loss on CT, although no bone loss was apparent at arthroscopy. There was a strong correlation between CT and arthroscopy with respect to the severity of glenoid bone loss (r = 0.79, 95% CI = 0.659-0.877, p < 0.0001). CT has both a high sensitivity and a high specificity for detecting glenoid bone loss, and agreement with arthroscopy regarding the severity of glenoid bone loss is good. CT can be used to assess glenoid bone loss and the need for bone augmentation surgery.